Education Policy as a Participatory Space: Reading Community Engagement Beyond Formal Approaches - Muhammad Zein; Muhammad Yunus; Bayanudin Sudin; Abdullah Abubakar; Adrian Kader (SAINTIS Publishing, 2025)
This research aims to analyze education policy as a participatory space by examining community involvement outside of formal approaches. The research uses a qualitative approach with a policy study design. Data was collected thru field observations, in-depth interviews with education actors and community members, and a review of relevant policy documents. The research results indicate that community participation in formal education policies is still dominated by procedural and administrative mechanisms, thus not providing adequate space for substantive involvement in decision-making. The relationship between schools and society tends to be hierarchical, which limits the bargaining power of society in determining the direction of education policy. On the other hand, more meaningful community participation is actually developing outside of formal approaches thru contextual and responsive community-based education initiatives that address local needs. This finding confirms that education policy needs to be understood as a social process that demands recognition and integration of community-based educational practices in order to create democratic and sustainable education policies.